Line Tracking Control of a Two-Wheeled Mobile Robot Using Visual Feedback. (25th March 2013) - Lee, G. H.; Jung, Seul
This article presents the development and control of a two-wheeled mobile robot as the base of a human carrier for an amusement/transportation vehicle. The robot has a combined structure of two systems: a line tracking mobile robot and an inverted pendulum system that maintains balance while following a line on the floor. The mobile robot is purposely designed to carry a human operator or humanoid arms. The robot has the capability to follow the line on the floor using visual feedback, as well as maintaining its balance on two wheels. A visual servoing technique allows the robot to follow the line on the floor captured by a camera as the desired trajectory. Controllers are designed to have good line tracking and balancing performance using sensor fusion techniques. Experimental studies involving the robot following a line demonstrate the feasibility of it being an amusement vehicle.